Beaver Pond Locations in Arctic Alaska, 1949 to 2020. - Ken Tape; Jason Clark; Benjamin Jones (Arctic Data Center, 2021)
Beavers were not previously recognized as an Arctic species, and their engineering in the tundra is considered negligible. Recent findings suggest that beavers have moved into arctic tundra regions and are controlling surface water dynamics, which strongly influence permafrost and landscape stability. These data show beaver pond locations in the Alaska Arctic identified in aerial photography and satellite imagery. Black and white aerial photography is from 1949-55, color infrared aerial photography (AHAP) is from 1976-84, and high-resolution satellite imagery is from 2000-2020. The number of beaver ponds doubled in most areas of ~2003 and ~2017 images. Earlier stages of beaver engineering are evident in ~1980 imagery, and there is no evidence of beaver engineering in ~1952 imagery, consistent with observations from Indigenous communities describing the influx of beavers over the period.